Cardiac implantable electronic devices with a defibrillator component and all‐cause mortality in left ventricular assist device carriers: results from the PCHF‐VAD registry. (13th August 2019) - Cikes, Maja; Jakus, Nina; Claggett, Brian; Brugts, Jasper J.; Timmermans, Philippe; Pouleur, Anne‐Catherine; Rubis, Pawel; Van Craenenbroeck, Emeline M.; Gaizauskas, Edvinas; Grundmann, Sebastian; Paolillo, Stefania; Barge‐Caballero, Eduardo; et al.
Abstract: Aims: To compare characteristics of left ventricular assist device (LVAD) recipients receiving a cardiac implantable electronic device (CIED) with a defibrillator component (implantable cardioverter‐defibrillator and cardiac resynchronization therapy with defibrillation, CIED‐D) vs. those without one, and to assess whether carrying such a device contiguously with an LVAD is associated with outcomes. Methods and results: Overall, 448 patients were analysed (mean age 52 ± 13 years, 82% male) in the multicentre European PCHF‐VAD registry. To account for all active CIED‐Ds during ongoing LVAD treatment, outcome analyses were performed by a time‐varying analysis with active CIED‐D status post‐LVAD as the time‐varying covariate. At the time of LVAD implantation, 235 patients (52%) had an active CIED‐D. Median time on LVAD support was 1.1 years (interquartile range 0.5–2.0 years). A reduction of 36% in the risk of all‐cause mortality was observed in patients with an active CIED‐D [hazard ratio (HR) 0.64, 95% confidence interval (CI) 0.46–0.91; P  = 0.012), increasing to 41% after adjustment for baseline covariates (HR 0.59, 95% CI 0.40–0.87; P  = 0.008) and 39% after propensity score adjustment (HR 0.61, 95% CI 0.39–0.94; P  = 0.027). Other than CIED‐D, age, LVAD implant as redo surgery, number of ventricular arrhythmia episodes and use of vasopressors pre‐LVAD were remaining significant risk factors of all‐cause mortality. Incident ventricular arrhythmias post‐LVAD portended a 2.4‐fold and 2.6‐fold increased risk of all‐cause and cardiovascular death, respectively; carrying an active CIED‐D remained associated with a 47% and 43% reduction in these events, respectively. Conclusions: In an analysis accounting for all active CIED‐Ds, including those implanted during LVAD support, carrying such a device was associated with significantly better survival during LVAD support.